Identification and treatment of patients with suspected penicillin allergy - Mateja Grošelj; Aleš Mrhar; Mihaela Zidarn; Mitja Košnik (Zdravniški Vestnik, 2013)
Background: Penicillin antibiotics are the most common medicines that are suspected to cause allergy. True penicillin allergy is rarely diagnosed in clinical practice. Many patients with a personal history of penicillin allergy are unnecessarily denied the benefits of penicillin and are given broader-spectrum antibiotics. Such unnecessary prescription of extended-spectrum antibiotics could contribute to the development and spread of multiple drug-resistant bacteria. The aim of our study was to check the identification and treatment of patients with a reported history of penicillin allergy. Methods: In the first part of the study, 21 pharmacies were included. Pharmacists asked adults who came to the pharmacy with a prescription for a non-penicillin antibiotic whether they are penicillin allergic and whether the allergy was confirmed with tests. In the second part of the study the antibiotic prescription pattern was surveyed in patients with ruled-out penicillin allergy. Results: 355/435 (81.6%) subjects, who came with the prescriptions for non-penicillin antibiotic, were patients – direct users of the prescribed antibiotic. Out of 124 patients with non-penicillin prescriptions, 26 (21%) claimed penicillin hypersensitivity, however, only in 7 (26.9%) it had been confirmed by allergy tests. Out of 272 patients with presumed penicillin hypersensitivity, diagnosis was confirmed in only 22 (8%). 61.4% patients with ruled-out penicillin allergy got a prescription for antibiotic in the previous year. However, in only 43.9% of cases these were penicillin antibiotics. Conclusion: We confirmed that many patients report penicillin allergy, however, the allergy is rarely confirmed by tests. Also, after tests that rule out penicillin allergy have been performed, penicillin antibiotics are still prescribed in lesser percent than other antibiotics. We found out that the vast majority of adults who come in the pharmacy with an antibiotic prescription are direct consumers of the prescribed antibiotic. Therefore, there is an opportunity to develop and implement a program of pharmaceutical care also for antibiotic treatment.